Team assisted individualization: enhancing students’ conjecturing skills in statistics and probability - Francisco, Kheigy Axl Ross Galapon; Esguerra Brillo, Danica Mae; Lazaro Quilang, Liezl Joy (International Journal of Evaluation and Research in Education (IJERE), 2025)
Many students struggle to understand mathematical concepts, leading to inadequate conjecturing skills. This study investigates the effectiveness of team assisted individualization (TAI), a cooperative learning approach, in improving these skills in mathematics. Utilizing a pre-test-post-test control group design, the research involved matched groups from two senior high school sections. Data were collected through tests and interviews conducted before and after the intervention, and analyzed using means, standard deviations, paired samples t-tests, analysis of covariance (ANCOVA), and content analysis. The findings indicate a significant enhancement in students’ conjecturing abilities following the implementation of TAI, even when controlling for their numerical reasoning skills. These results demonstrate that TAI is more effective than traditional lecture-discussion methods (LDM) in promoting conjecturing skills. Consequently, this study encourages educators to explore and adopt TAI strategies to better facilitate the development of students’ mathematical reasoning and conjecturing capabilities.